2011
DOI: 10.4323/rjlm.2011.73
|View full text |Cite
|
Sign up to set email alerts
|

"Legal highs" in Romania: historical and present facts

Abstract: In the modern history of our country, the subject of psychoactive substances was banned as being against the socialist-communist political ideology, and consequently the research and knowledge on the historical evolution of the use of plants and substances for medical, hedonistic and/or ritual purposes in our country was not given any encouragement. In this context of a diluted and outdated knowledge on the psychoactive substances which had been maintained for decades, the explosion of the drug addiction pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…It was found that NPS users, more often than non-NPS users, were admitted to hospital through emergency, which indirectly confirms the observations of other re-study by Sutherland et al [22], in which a similar group was described (regular psychostimulant users), with 41.9% of respondents reporting NPS use. In Europe, NPS have been reported mostly among heavy drug users, specifically in Hungary and Poland [20,28,29]. A Polish survey reported that 15% of the clients of needle and syringe programs marked NPS as their "most problematic substance," while 12% had used mephedrone in the month preceding the survey, and 14% had used other NPS [30].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that NPS users, more often than non-NPS users, were admitted to hospital through emergency, which indirectly confirms the observations of other re-study by Sutherland et al [22], in which a similar group was described (regular psychostimulant users), with 41.9% of respondents reporting NPS use. In Europe, NPS have been reported mostly among heavy drug users, specifically in Hungary and Poland [20,28,29]. A Polish survey reported that 15% of the clients of needle and syringe programs marked NPS as their "most problematic substance," while 12% had used mephedrone in the month preceding the survey, and 14% had used other NPS [30].…”
Section: Discussionmentioning
confidence: 99%
“…The number of cases are similar with the ones obtained in the last years; for example for example in 2009 in living persons out toxicology lab gave 35 positive results for drugs of abuse (17 opiates, 7 THC, 3 ketamine, 8 -others); in 2010 we find a decrease in the number of opiates cases (14 cases) and a marked increase in the number of TCH cases (17). A phenomenon becoming increasingly more prevalent in the last 1-2 years is a shift from "classical drugs" to "legal highs" [2,[4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…However, in almost all cases in which legal highs were considered to be involved in thanatogenesys (as suggested by clinical investigation or crime scene investigation), we were able to find classical high-risk drugs lik opiates, ketamine, etc. The main causes for this phenomenon, after Gorun et al are: (1) sprinkling drugs bought from "legal shops" with high risk drugs, or (2) a concomitant or successive use of legal highs and classical drugs of abuse [8].…”
Section: Vol XIX No 3(2011)mentioning
confidence: 99%
“…By only comparing the first ten months, the difference is also extremely high (70 cases in the last ten months of 2010). The most likely explanation is an increased use of legal highs (herbal highs, "legal" drugs) [15][16][17][18], but better preventive measures may play a part as well. DRDs associated with legal highs were not identified.…”
Section: Discussionmentioning
confidence: 99%